(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The occupation and appropriation of urban space, in the artistic and aesthetic field, are configured in a plural and multifaceted way; proving, more and more, the power of space as a field open to experimentation. To broaden this dialogue, this article aims to reflect on some issues that underlie these initiatives that use heritage in its multiple dimensions - both material and immaterial -, and the interrelationships with the actions and knowledge of popular culture. As a background, the works carried out in two different contexts will be analyzed, however, with similar characteristics regarding the relations between art, city and heritage: Coletivo Cantareira, which is a community movement committed to continuing some traditions and singularities of Ilha de Paquetá, RJ, and the Grupo de Teatro São Gonçalo do Bação made up by residents of the rural district of São Gonçalo do Bação, in the city of Itabirito-MG, which, due to its artistic and cultural dynamics, constitutes itself as a group of Theater and Community.